The 9/11 decade media discourse: content analysis on correspondents’ reports in Al Jazeera online / Noratikah Mohamad Ashari and Mokhtar Mohammad - Mohamad Ashari, Noratikah; Mohammad, Mokhtar (CMIWS and UiTM Press, 2014)
Adopting the theory of second level agenda-setting, this study interprets the main themes in 18 articles extracted from a special report on the 9/11 Decade in Al Jazeera online. The main aim of this study is to acknowledge that media agenda-setting theory is applicable to the contents in the Correspondents’ Reports articles from Al Jazeera online regarding the post 9/11 decade. It also aims to raise awareness that the discourse of Terrorism Alertness and Fearthemes are frequently used in these articles.